La prolifération nucléaire : une relecture théorique - Fortmann, Michel (Études internationales, 1993)
This article, which runs counter to traditional studies on non-proliferation, starts from the premise that it will be impossible to force the nuclear genie back into the lamp from whence he came. In the future, management of nuclear energy for military purposes will demand not a laisser-faire policy, as K. Waltz has stressed, but, at the very least, a constructive dialogue with the new candidates for membership in the nuclear club. It will be necessary, on this more cooperative basis, to redefine the rules of non-proliferation in favour of measures for regional stabilization and confidence-building. Only such a way forward will prevent the 21 st century from becoming the century of the nuclear mob.